Evaluation of Solar Photosensitised River Water Treatment in the Caribbean - K. Tota-Maharaj; D. E. Meeroff (International Journal of Photoenergy)
An economical supply of hygienic potable water is one of the most pressing public health issues facing developing countries in the Caribbean region today. This project investigates the performance of a novel solar photochemical reactor for disinfecting river water. The prototype photochemical reactor was designed, constructed, and tested for the microbiological degradation of faecal coliform present in River Water. The experiments evaluated the efficacy of two photosensitive dyes (malachite green and methylene blue) as agents for detoxification with concentrations ranging from 0.5 to 3.0 mg/L. The photochemical reactor operated in a single-pass mode and compared the disinfection rates with direct photolysis. The photosensitizers showed a high efficacy rate using natural sunlight with microbial reduction ranging from 97 to 99% for concentrations as low as 0.5 mg/L of dye. The sensitizers were found to be photobleaching and were very effective at lower concentrations (<2.0 mg/L). Direct photolysis inactivation rate constants were 0.034 and 0.046 min−1, whilst degradation rates using methylene blue ranged from 0.057 to 0.088 min−1 and for malachite green from 0.057 to 0.086 min−1, respectively. One-way ANOVA was tested between the inflow and outflow pH, as well as the degradation rates constants for both photosensitisers with P>0.01. Post-solar disinfection included the use of a coconut fiber filter which polished the water removing residual dye concentrations and bacterial contaminants.